Regulating Anions in the Solvation Sheath of Lithium Ions for Stable Lithium Metal Batteries - Zhang, Xue-Qiang; Chen, Xiang; Hou, Li-Peng; Li, Bo-Quan; Cheng, Xin-Bing; Huang, Jia-Qi; Zhang, Qiang (ACS energy letters, 2019)
Safe lithium (Li) metal batteries have been plagued by dendrite growth due to a heterogeneous solid electrolyte interphases (SEI) on the Li metal anode. Modulating the solvation sheath of Li ions enhances the uniformity and stability of SEI significantly. However, anion regulation in the solvation sheath for constructing stable SEI is rarely touched. Herein, the solvation structure of original bis(fluorosulfonyl)imide (FSI–) anions in the solvation sheath is altered by introduction of other anions, promoting the complete decomposition of FSI– and forming a stable SEI on the Li metal anode. Moreover, both the oxidation stability window of the electrolyte and current collector protection were enhanced. Furthermore, the components and structure of the solvation sheath were disclosed by combining 17O nuclear magnetic resonance and molecular dynamics simulations. This work provides fresh insight into the interrelation among various anions on regulating the solvation sheath of Li ions and demonstrates guidance in rationally designing electrolytes for stable and safe Li metal batteries.